Women's Empowerment in Agriculture Index (WEAI) Pilot for Guatemala - Peterman, Amber; Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Dardón, Monica; Hassan, Md. Zahidul; Kamusiime, Herbert; Malapit, Hazel J. (International Food Policy Research Institute, 2012)
The Women’s Empowerment in Agriculture Index (WEAI) is a composite measurement tool that indicates women’s control over critical parts of their lives in the household, community, and economy. It allows us to identify women who are disempowered and understand how to increase autonomy and decisionmaking in key domains. The WEAI is also a useful tool for tracking progress toward gender equality, which is one of the Millennium Development Goals. The WEAI measures the empowerment, agency, and inclusion of women in the agriculture sector in an effort to identify ways to overcome those obstacles and constraints. The Index is a significant innovation in its field and aims to increase understanding of the connections between women’s empowerment, food security, and agricultural growth. The Guatemala pilot was conducted in the country’s Western Highlands, in the departamentos (departments) of El Quiché, Huehuetenango, Quetzaltengo, San Marcos, and Totonicapán—areas with a high concentration of indigenous populations.